2022
DOI: 10.3389/fdgth.2022.880055
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Technological Divide: Stigmas and Challenges With Technology in Digital Brain Health Studies of Older Adults

Abstract: The COVID-19 pandemic has increased adoption of remote assessments in clinical research. However, longstanding stereotypes persist regarding older adults' technology familiarity and their willingness to participate in technology-enabled remote studies. We examined the validity of these stereotypes using a novel technology familiarity assessment (n = 342) and with a critical evaluation of participation factors from an intensive smartphone study of cognition in older adults (n = 445). The technology assessment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
(21 reference statements)
4
17
0
1
Order By: Relevance
“…These results are consistent with previous findings from McWilliams and colleagues who deployed the same dry EEG technology in a separate cohort of 89 healthy older adults and reported high adherence and usability scores (e.g., mean adherence of 82% and mean SUS score of 78.7) (52). Our compliance levels are also slightly higher than those observed in purely cognitive remote studies using smartphone for repeated testing [e.g., adherence of 85.7% (32)]. As discussed by Moore et al, it is likely that our older participants' high adherence rate is due to a combination of extrinsic factors including the ease-of-use of the technology, and intrinsic factors such as personal motivation (the older cohort self-referred into our study) (63).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with previous findings from McWilliams and colleagues who deployed the same dry EEG technology in a separate cohort of 89 healthy older adults and reported high adherence and usability scores (e.g., mean adherence of 82% and mean SUS score of 78.7) (52). Our compliance levels are also slightly higher than those observed in purely cognitive remote studies using smartphone for repeated testing [e.g., adherence of 85.7% (32)]. As discussed by Moore et al, it is likely that our older participants' high adherence rate is due to a combination of extrinsic factors including the ease-of-use of the technology, and intrinsic factors such as personal motivation (the older cohort self-referred into our study) (63).…”
Section: Discussionsupporting
confidence: 92%
“…No clear evidence of usability barrier in the older cohort was found as attested by the lack of differences in usability scores between the two groups. This result is in agreement with findings from Nicosia and colleagues who reported that, while older age is associated with less technology familiarity, older adults are willing and able to participate in technology-enabled studies (32). The high percentage of successful sessions in the older cohort also underlines that the ease-of-use of the platform was satisfactory and enabled populations who were not digital natives to use the system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Technology familiarity was assessed with a novel measure described in Nicosia et al (2021). Briefly, the assessment combined objective measurements of technology knowledge (technology-related icon recognition) and self-reported ratings of (1) the frequency with which they perform certain smartphone tasks and (2) how difficult it would be for them to perform various technology-related tasks.…”
Section: Methodsmentioning
confidence: 99%
“…demand characteristics, “white coat” testing effects), bolster sample size and diversity, and make participation more accessible and inclusive for individuals who may otherwise be unable to come into the laboratory or clinic. Indeed, interest in smartphone studies is growing, and several studies have demonstrated the feasibility and validity of smartphone-based assessments for use in older adults and individuals with preclinical AD (GĂŒsten et al, 2021; Hassenstab et al, 2020; Lancaster et al, 2020; Mackin et al, 2018; Nicosia et al, 2021; Öhman et al, 2021; Papp et al, 2021; Wilks et al, 2021), as well as the potential for high-frequency in-home monitoring to substantially increase the statistical power of therapeutic trials (Dodge et al, 2015).…”
Section: Introductionmentioning
confidence: 99%